STUDENTS’ PROBLEMS IN ANSWERING LISTENING SECTION OF TOEFL AT NON ENGLISH STUDY PROGRAM OF UPN VETERAN JAKARTA - Cut Fitariana; Abduh - Almanar; Abdul Rohim (Universitas Muhammadiyah Tangerang, 2021)
This research aimed to find the problems that students did in answering TOEFL especially in listening section. The research used descriptive qualitative approach. For the data collection, it used the instrument is interview. The subjects of the research were non english department students in seventh grade of FIKES Universitas Pembangunan Nasional Veteran Jakarta. To analyze the data, it was through the techniques: data collection, data display, data reduction, and conclusion drawing. 25 seventh semester students of Nursing Study Program participated in this study selected by using random sampling techniques. Descriptive qualitative method was used in this research. The results of this research indicate that the difficulties experienced by students based on the the interview are difficultiy in their concentration while listening, difficulty regarding vocabulary meaning, difficulty in catching meaning in long and speed conversation, and difficulty in recognizing unfamiliar topic.